105k views
2 votes
What is the solution to the equation 3 (2 x + 5) = 3 x + 4 x?

2 Answers

2 votes

Answer:


\boxed {x = 15}

Explanation:

Solve for
x:


3(2x + 5) = 3x + 4x

-Use Distributive Property:


3(2x + 5) = 3x + 4x


6x + 15 = 3x + 4x

-Combine like terms:


6x + 15 = 3x + 4x


6x + 15 = 7x

-Take
7x and subtract it from
6x:


6x + 15 - 7x = 7x - 7x


-x + 15= 0

-Subtract
15 on both sides:


-x + 15 - 15 = 0 - 15


-x = -15

-Take
-x and divide it on both sides:


(-x)/(-1) = (-15)/(-1)


\boxed {x = 15}

So, therefore, the value of
x is
15.

User Mark Kenny
by
5.9k points
2 votes

Answer:

15 = x

Explanation:

3 (2 x + 5) = 3 x + 4 x

6x + 15 = 7 x

15 = 7 x - 6x

15 = x

User Brendan Wood
by
5.8k points